Study On Practice Swarm Optimization Based Search Algorithms For Network Shortest Path Problems - W.muhemmed, Ammar (2007)
The purpose of this research is to investigate on the use PSO for solving the unconstrained and constrained shortest path problems commonly encountered in network graph theory.